Current perspectives on citizenship education or a belated contribution to two almost overlooked 100th anniversaries, the common theme of which is institutional civic education in our countries - Stanek, Antonin (Civilia, 2023)
The study tries to indicate a possible answer to the question of why we need quality civic education and why it should remain a worthy part of the curricula at the second level of primary schools. We will look for the answer against the background of current social changes and through the inspiration of the author M. S. Branson, who at the end of the last century dealt with a similar question at the Center for Civic Education in California. We base our view of the future on the current social context, especially after the year 2000, in which institutional citizenship education was formed and especially implemented.
Keywords: Civic education; Citizenship education; Civic knowledge; Civic skills; Civic disposition